Nocturnal loss of NOx during the 2010 CalNex‐LA study in the Los Angeles Basin. Issue 22 (28th November 2014) - Tsai, Catalina; Wong, Clare; Hurlock, Steve; Pikelnaya, Olga; Mielke, Levi H.; Osthoff, Hans D.; Flynn, James H.; Haman, Christine; Lefer, Barry; Gilman, Jessica; de Gouw, Joost; Stutz, Jochen
Abstract: The chemical removal of NO x at night in urban areas remains poorly constrained due to uncertainties in the contribution of various loss pathways and the impact of the suppressed nocturnal vertical mixing. Here we present long‐path differential optical absorption spectroscopy observations of nocturnal vertical concentration profiles of O3, NO2, and NO3 in the lower atmosphere (33–556 m above ground level) measured during the CalNex‐LA 2010 study. Positive nocturnal vertical gradients of O3 and NO3 and negative gradients of NO2 were observed during the night. Relatively short lifetime of nocturnal NO3 (less than 1000 s) and high nighttime steady state N2 O5 mixing ratios (up to 2 ppb) indicated active nocturnal chemistry during CalNex. Comparison of modeled and observed altitude‐resolved NO3 loss frequencies shows that hydrolysis of N2 O5 on aerosols was the dominant loss pathway of NO3 and NO x . Based on this argument, the nocturnal loss rates of NO x, L (NO x ), at different altitudes and averaged over the lowest 550 m of the atmosphere were calculated. The nocturnally averaged L (NO x ) ranged between 0.8 and 1.3 ppb h −1 for the lower atmosphere with the L (NO x ) for the first 8 days at about 1 ppb h −1 . This number is close to the one previously determined in Houston in 2009 of 0.9 ppb h −1 . Comparisons between daytime NO x loss due to the OH + NO2 reaction and nighttime L (NO x ) show that during CalNex, nocturnal chemistry contributed an average of 60% to the removal of NO x in a 24 h period in the lower atmosphere. Key Points: Nocturnal chemistry and the loss of NO x at night are altitude dependent Nocturnal NO x loss in Los Angeles proceeds through aerosol uptake of N2 O5 Height‐averaged nocturnal loss of NO x is comparable to OH + NO2 daytime loss